2016
DOI: 10.4049/jimmunol.1600829
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Sensitization Underlies Hyperreactive Antigen-Specific CD4+ T Cell Responses in Coincident Filarial Infection

Abstract: Among the various hypotheses put forward to explain the modulatory influence of helminth infection on allergic effector responses in humans, the IL-10 induced suppression of Th2-associated responses has been the leading candidate. To explore this helminth/allergy interaction more fully, parasite- and allergen--specific T cell responses CD4+ T cell responses in 12 subjects with filarial infections and coincident allergic sensitization (Fil+A+) were compared these to the responses to 3 appropriate control groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 76 publications
0
19
1
Order By: Relevance
“…Interestingly, CD4 T cells coexpressing IFN-γ and TNF-α and harboring a phenotype of effector-memory response were associated with active tuberculosis in HIV-uninfected [ 68 , 69 ] and HIV-infected TB patients [ 67 ]. Of note, polyfunctional helminth-specific CD4 T-cell responses were also recently associated to helminth biological activity [ 47 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CD4 T cells coexpressing IFN-γ and TNF-α and harboring a phenotype of effector-memory response were associated with active tuberculosis in HIV-uninfected [ 68 , 69 ] and HIV-infected TB patients [ 67 ]. Of note, polyfunctional helminth-specific CD4 T-cell responses were also recently associated to helminth biological activity [ 47 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have previously shown by using cells from Loa loa-infected travelers, who present clinically with allergic-type symptoms much more frequently than those born and bred in Loa loa-endemic regions of the world (78,79) and who had evidence of HDM allergic sensitization prior to the acquisition of their filarial infection, that there was a marked expansion of parasite antigen-specific CD4 + Th2 cells that were in turn associated with marked elevation of IgE and eosinophilia, in comparison with nonallergic but Loa loa-infected patients (39). Like these travelers, our data from this murine system suggest that allergic sensitization coincident with helminth infection drives an exaggerated eosinophil-rich pulmonary type 2 immune response in the lungs, mediated predominantly by the allergic sensitization that occurs In a primary exposure to Ascaris parasites, after penetrating the intestine at the level of the cecum or proximal colon, the infective L3-stage larvae migrate through the portal vessels to the liver and subsequently to the lungs in their quest to reach the airways.…”
Section: Methodsmentioning
confidence: 96%
“…Moreover, larvae Human population shifts have led to a reexamination of how helminth infections and allergy interface given that for many people allergic sensitization has preceded the acquisition of the helminth infection. Indeed, we have previously demonstrated that allergic sensitization to house dust mites (HDM), an environmental allergen, prior to the acquisition of a human filarial infection induces a markedly exaggerated parasite antigen-specific Th2-associated immune response (39). We hypothesized that this exaggerated type 2-dominated immune response could play a vital role in limiting parasite burden at the expense of parasite-associated morbidity.…”
Section: Hdm Sensitization Followed By Ascaris Infection Inhibits Larmentioning
confidence: 99%
“…For helminth infection in humans, the immune response during the early/acute phase of infection involves the induction of type 2-associated cytokines (IL-4, IL-5, IL-9, and IL-13) first by innate lymphocytes (ILC2) and later by effector antigen-specific polyfunctional CD4 T cells 32 . This relatively early phase also induces high antigen-specific IgG4 and IgE levels as well as peripheral and tissue eosinophilia and expanded populations of AAM 33 , 34 .…”
Section: Acuteness and Chronicity Of Infection Drive Distinct Immune mentioning
confidence: 99%